Uso de subproductos de cosecha de cacao, palma aceitera y raquis de banano en la producción de humus con lombriz roja californiana (Eisenia foetida) - Méndez Peña, Homero Ismael (2015)
In order to evaluate the use of cocoa crop byproducts, oil palm and banana rachis, more and sawdust cattle manure in the production of humus with Californian red worm (Eisenia foetida). field research was carried using a completely randomized design with 4 treatments and 4 repetitions Once the ANOVA statistical significance for high repetitions and treatments was determined. Treatment with 50% EB + 25% AB + 8.3% + 8.3% CC 8.3% RB RP had the highest value of average height bed with a value of 30 cm, which resulted value statistically equal to the average of 50% EB + 25% + 25% CC AB, with 25.8 cm, The highest average pH value was recorded in the treatment with 50% EB + 25% AB + 8.3% RB DC + 8.3% + 8.3% RP with 7.75, this value being statistically equal to other treatments which had values of 7.39 values for EB + 50% 25% 25% AB + RB, 7.37, the increased production of humus was made in the treatment EB + 25% AB + 8.3% + 8.3% CC 8.3% RB RP with a value of 1500.00 kg in the composition Humus chemistry higher levels of nitrogen and potassium were achieved by treatment with that obtains 1.54% nitrogen and 1.81% for potassium, treatment with 50% EB + 25% AB + 8.3% CC + 8 3% + 8.3% RP RB reported the highest value with 3.06% phosphorus and 1.27% sulfur. Treatment with EB50% + 25% + 25% AB CC has the highest value in the elements calcium and magnesium with 4.21% 1.07% relative to the higher value organic matter treatment registers 45, 6% in the economic analysis the treatment with 50% EB + 25% AB + 8.3% + 8.3% CC 8.3% RB RP presented higher costs to $ 134.31 and lower costs were obtained treatment with EB + 25% + 25% AB CC $ 127.31. The treatment reported the largest income was 50% EB + 25% AB + 8.3% + 8.3% CC 8.3% RB RP with $ 375.00 and lowest income 50% treatment EB + 25% AB + 25% RP to $ 152.62. Most cost / benefit ratio is presented in the EB treatment with 50% + 25% AB + 8.3% + 8.3% CC 8.3% RB RP with 1.79.